Penelitian Mengenai Metode Steganografi Least Significant Bit - Ivan Jonathan; Albert Yeusiawan Haryono; Kevin Leonardi (Ultima Computing : Jurnal Sistem Komputer, 2017)
In today's technological era, the concealment of sensitive information is the concern of many people. Because the information is often shared and discussed through a very commonly used communication medium. Steganography is one technique to hide a secret message into a file that has a larger size. In this paper, we will discuss the methods that can be used in steganography, especially the method of Least Significant Bit. Keywords: Steganography, Data Hiding, Steganography Algorithm, Least Significant Bit.